Spatial Competition, Spatial Agglomeration and Survival of Small Businesses in Milan During COVID-19 - Türk, Umut; Östh, John (Societa Editrice Il Mulino, 2023)
This study examines the location choice of small firms in Milan across three periods: pre-COVID, early COVID, and late COVID, testing the applicability of traditional spatial economic theories. With the recent COVID-19 pandemic restricting human mobility, there has been a significant acceleration of tele-activities such as remote work and e-commerce, which may have impacted consumer behavior and service supply. Using data extracted from open map services, we find that small businesses have become more residential but moved farther from the city center during the pandemic, with single-owned and multi-branch firms exhibiting different responses. © 2023 Elsevier B.V., All rights reserved.
Keywords: Central Place Theory; Hotelling's Theory; Retail Location; Hotelling’s Theory